Pricing and price policy - Blythe, James (Henry Stewart Talks, 2012)
Price and the bottom line, The pricing process, Setting price objectives, Pricing strategy, Pricing for co-dependent products, Pricing in grey markets, Customer perception of price, Factors affecting price sensitivity, Costs and pricing, Pricing for competitive advantage, Cost-based pricing, Price adjustment strategies, Customer-based pricing, Demand pricing, Product line pricing, Skimming, Psychological pricing, Second-market discounting, Competitor-based pricing, Pricing in international markets, Legal issues in pricing, Pricing in business-to-business markets